Rural response system to prevent violence against women: methodology for a community randomised controlled trial in the central region of Ghana - Adolphina A. Addo-Lartey; Deda Ogum Alangea; Yandisa Sikweyiya; Esnat D. Chirwa; Dorcas Coker-Appiah; Rachel Jewkes; Richard M. K. Adanu (Taylor & Francis Group, 2019)
Violence against women (VAW) is common in Ghana, with nation-wide surveys reporting high prevalence of intimate partner violence (IPV) (physical, sexual and/or emotional violence). Our trial assesses the community level impact of the Rural Response System which uses Community-Based Action Teams 'COMBAT' for preventing VAW in Ghana. This study is a mixed method unmatched cluster randomised controlled trial and includes rural (n = 23), peri-urban (n = 7) and urban (n = 10) communities in four districts of the Central Region, Ghana. The trial will last three years with one baseline survey, one impact assessment and a qualitative baseline, midpoint and endline evaluation. A total of 40 localities were selected to serve as clusters (20 per trial arm) with about 82 households per cluster recruited at baseline. The same number will be recruited post-intervention. Adult women (18 to 49 years) and men (≥ 18 years) were drawn from different localities. Sampling of households within a community was random and done using a computerised system. In each selected household, one female or male resident was invited to participate. Individuals are eligible for inclusion in the study if they usually live (sleep and eat) in the household, have lived in the community for at least a year, and are between the ages of 18-to-49 years old. Our impact assessment component will compare past 12 months incidence of IPV (i.e. IPV experiences for women and perpetration of physical and/or sexual IPV for men) between arms in the trial. The implementation of this community trial comes at an opportune time when evidence on the effectiveness of a targeted VAW intervention in the Ghanaian society is needed to inform the development of national policies for preventing VAW. Our progressive research approach using a mixed method design will further extend knowledge globally on a multifaceted intervention to reduce the incidence of intimate partner violence in a developing country. Trial registration: ClinicalTrials.gov identifier: NCT03237585.